Analysis of propionibacterium acnes-induced non-specific immunity to Trypanosoma brucei in mice - Black, Samuel J.; Murray, M.; Shapiro, S.Z.; Kaminsky, R.; Borowy, N.K.; Musanga, R.; Otieno-Omondi, F.P. (Wiley, 1989)
Summary Mice treated with dead Propionibacterium acnes (previously called Corynebacterium parvum), up to 30 days before infection with any of three strains of Trypanosoma brucei, were more able to limit the level of first‐wave parasitaemia than untreated controls. Reduced parasitaemia was not due to enhanced phagocytosis of input parasites and was associated with a dramatic reduction in the proportion of multiplying T. brucei in the blood of treated as compared to control mice. For 4 days after P. acnes treatment, T. brucei growth‐inhibitory molecules, assayed by their effect on T. brucei multiplication under axenic culture conditions, were detected in the serum of recipient mice. The molecules were released by macrophages collected from the peritoneal cavity of P. ac/ies‐treated mice, and similar molecules were produced in vitro by macrophages from normal mice after incubation with P. acnes. Accessory studies suggested that the molecules were breakdown products of P. acnes and were unlikely to be responsible for the long‐term in‐vivo effects of the P. acnes treatment. It was also shown that monokines and lymphokines which are likely to be induced by in‐vivo P. acnes treatment, i.e. IL‐1, IL‐2, TNFα, INFα, INFβ, INFy, PGE1, PGE2, PGF2, and biological mediators present in Con‐A and LPS‐induced spleen cell supernatants (collected 20, 40, 60 or 80 h after mitogen stimulation) had no influence on T. brucei growth under axenic culture conditions over a wide range of concentrations. The studies suggest that the P. acnes effect was not due to a direct interaction of these biological mediators with the T. brucei. We suggest that the reduction in T. brucei parasitaemia in P. acnes‐treated mice reflects secondary physiological effects of one or more unidentified biological mediators.